The Inovasi Curcuma Longa terhadap Urgensi Epizootik Penyakit Mulut dan Kuku pada Ternak Sapi Menjelang Idul Adha - Bawono, Bagas Trikuncoro (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2024)
FMD (Foot and Mouth Disease) in Cattle has become an Epizootic in Indonesian society. FMD is very easy to spread in a cattle community, giving rise to an epizootic. This triggers panic on both the buyer and trader side of the cow ahead of Eid al-Adha which will be held on July 10 2022. This literature review aims to increase public awareness and government sensitivity regarding the impact of the recent FMD outbreak and provide an overview of the effect of Curcuma longa on increasing the body's immunity so that it can prevent the spread of FMD (mouth and foot disease) in cattle. The method used is literature review. Article sources were obtained through several databases such as Google Scholar, ProQuest, Sciencedirect, Pubmed, Scopus which were published in 1997 to 2022. The author finds that the number of FMD cases that infect livestock such as cows, buffaloes, goats and pigs has experienced a regular increase in the number of cases. On the other hand, the authors found that Curcuma longa extract could stimulate the production of various types of cytokines, including IFN-γ and IL-2. Therefore, with the increasing number of FMD epizootic cases in Indonesia, the authors conclude that Curcuma longa can be used as a curative effort in eradicating the spread of the FMD virus